(untitled) (Pakistan Journal of Science, 2022)
The conventional way of preparing students for the lab work is to encourage them to read manual for the lab wok, but this procedure typically overloads their working memory with the information. On the other hand only a limited number of students try to understand or do read the manuals before entering into the laboratory. The present study was designed to explore “The impact of pre-labs in chemistry laboratory at secondary level”. Sample of this study consists of boys (n =119) and girls (n=116) studying chemistry at secondary school level. Boys sample was further divided into control group (n= 65) and experimental group (n=54). Similarly, girls sample was divided into control group (n=55) and experimental group (n =61). Pre-labs and post-labs were developed, keeping in view information processing model for teaching-learning science and Bloom Taxonomy of Educational Objectives. Data collection was continuous through out the academic session till the eighteen experiments were completed. The data were analyzed, by using SPSS. T-test applied at 0.05% level of significance. Study revealed that Pre-lab has improved student’s understanding in chemistry lab. It is also indicated that Pre-lab has strong effect in improvement of academic achievement of boys than that of girls.